Evaluation of Cardioprotective activity of Asparagus racemosus against Doxorubicin induced cardiotoxicity in albino rats: an experimental study - Vishwakarma, Pinki; Chatterjee, Manisha; Sharma, Monica; Saini, Manish; Goel, Rajkumar; Saxena, K. K. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Cardiotoxicity is one of the most feared side effects of anticancer agents like Doxorubicin. Asparagus racemosus is a widely used medicinal plant in Indian system of medicine known for its antioxidant activity. In certain studies ethanol extract of Asparagus racemosus has shown to possess cardioprotective activity in experimental animals while in some other studies cardioprotective potential of Asparagus racemosus has not been demonstrated. Therefore, due to the controversial action, the present study was designed to explore the cardioprotective effect of aqueous effect of Asparagus racemosus against doxorubicin induced cardiotoxity. Methods: Following approval from Institutional Animal Ethics Committee of L.L.R.M Medical College registered under CPCSEA, India, this study was conducted in which 30 rats were randomized into five groups of six rats each. Group I received 2 ml/kg b.w. normal saline p.o for 21 days, group II apart from receiving pellet diet and normal saline for 21 days were treated with Doxorubicin in a single dose of 20 mg/kg intraperitoneally on the 21st day, group III and group IV received aqueous extract of Asparagus racemosus in doses of 250 mg/kg/day and 500 mg/kg/day respectively p.o. for 21 days followed by administration of Doxorubicin (20 mg/kg i.p.) on the 21st day, Group V received Carvedilol in doses of 30 mg/kg/day p.o. for 21 days followed by administration of Doxorubicin (20mg/kg i.p) on the 21st day. Then they were anaesthetized and blood sample was collected from abdominal aorta for performing blood test i.e. Creatinine kinase MB fraction (CK-MB), Lactate dehydrogenase (LDH), Serum glutamate oxaloacetate transaminase (SGOT), Serum glutamate pyruvate transaminase (SGPT). After blood collection the animals were sacrificed and heart was dissected out for histopathological study. The data obtained was organized and analysed by suitable statistical methods i.e. ANOVA followed by Post Hoc test. Results: CK-MB, LDH, SGOT and SGPT levels were found to be significantly raised (p<0.001) in Doxorubicin treated group. Asparagus racemosus pretreated groups exhibited significant limitation (p<0.001) in rise in levels of CK-MB,LDH,SGOT and SGPT levels in a dose dependent manner following Doxorubicin administration which were comparable to the group treated with the standard cardioprotective drug Carvedilol. Histopathological changes further corroborated cardioprotective potential of Asparagus racemosus. Conclusions: The present study concluded that aqueous extract of Asparagus racemosus possess cardioprotective potential against Doxorubicin induced cardiotoxicity.